First reconstruction of the dietary traits of the Mediterranean deer ( Haploidoceros mediterraneus ) from the Cova del Rinoceront (NE Iberian Peninsula) - Rivals, Florent (2018)
This article presents the results of the reconstruction of the paleodietary traits in the Mediterranean deer (Haploidoceros mediterraneus) from the MIS 5 site of Cova del Rinoceront in the NE of the Iberian Peninsula. This medium-sized deer species has a poor fossil record in Europe, and only four localities have reported remains. This study is the first approach to the dietary traits of this genus. Our data reveal that H.mediterraneus hadmixed feeding traits,with clear tendency toward leaf browsing, similar to the extant fallow deer (Dama dama).We also report a probable phenomenon of competitive exclusion between H. mediterraneus and D. dama at all localities where the presence of H. mediterraneus has been reported so far (Cova del Rinoceront, PRERESA, Igue des Rameaux, and Lunel-Viel).